Perbaikan Kesuburan dan Kualitas Tanah Bekas Ubikayu Melalui Pengembalian Biomassa Kacang Tanah dan Jagung - Wijanarko, Andy; Purwanto, Benito Heru; Shiddieq, Dja’far; Indradewa, Didik (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2017)
Continuous planting of cassava can reduce soil fertility and yield of cassava. Returns of plant biomass can reduce the rate of decline in soil fertility. This study aims to determine the effect of the return of groundnut biomass in improving soil fertility and soil quality at cassava land. Laboratory and greenhouse studies have been conducted in Iletri Malang. Laboratory studies to determine the mineralization of N, experiment using a completely randomized design with three replications. The treatment consists of : the first factor (origin biomass): groundnut, maize, groundnut, maize 1: 1 (w/w), groundnut - maize 2: 1 (w/w), groundnut - maize 1: 2 (w/w) and without biomass, while the second factor (duration of land utilization for cassava): less than 10 years and more than 30 years. N mineralization estimated using first order equations. Greenhouse experiment using a randomized block design with treatment as same as with laboratory experiments. Parameter observations greenhouse experiment was pH, N and C in total, NH4+, NO3-, N labile fractions, C labile fractions and uptake of N, P, K. The results showed that application of groundnut : maize biomass ( 2: 1), increase the rate of mineralization (K) by 43% -56% and increase the amount of N mineralized (N0) by 171-222% as compared with no biomass application. Application of groundnut : maize biomass (1: 1) or groundnut : maize biomass (2: 1) is able to improve soil fertility as reflected by the increasing availability of total N, C-organic, NH4 + and NO3, improve the soil qualityÂ with increase in the soil quality parameters ( N and C labile fractions), andÂ increases of the uptake of N, P and K by cassava. Returns biomass either groundnut mixed with maize or not, has the potential to restore soil fertility.